Recent advances in crocodilian oil research: bioactive components and potential therapeutic applications - Huang, Yuxi; Zheng, Xinyue; Ming, Xingchen; Jiao, Qiqi; Xiao, Weihao; Wu, Qian; Zheng, Linyang; Zeng, Yunfu; Cheng, Shaowen; Wang, Rong; Yang, Jian; Bian, Yangyang; et al. (Frontiers in Medicine, 2025)
The economic value of crocodilian farming has risen substantially in recent years, drawing increasing attention to crocodilian oil as a traditional natural remedy rich in diverse bioactive constituents. Despite its therapeutic potential, crocodilian fat remains underutilized, and its nutritional and medicinal properties have not been widely recognized. This review provides a bibliometric analysis of past research trends and highlights current developments related to crocodilian oil. Recent advances in the characterization of its physicochemical properties and health-related applications are summarized. The primary biological activities of this oil are attributed to its high unsaturated fatty acid and stearic acid contents. Emerging evidence supports its anti-inflammatory, antimicrobial, and scar-reducing effects mediated through key signaling pathways, including p38 mitogen-activated protein kinase, transforming growth factor-β1/Smad3, and AMP-activated protein kinase. Reported benefits include improvements in skin conditions and the modulation of energy metabolism. Potential applications encompass adjunctive treatment for Candida albicans infections, topical anti-inflammatory agents, moisturizers, and permeability enhancers in cosmetic formulations, and dietary oil substitutes for managing hypertriglyceridaemia and metabolic disorders affecting the liver and brain. Challenges and future research directions in this field are also discussed.